IDENTIFICATION OF FARMER NEEDS ON TECHNOLOGY INNOVATION FOR BUFFALO DEVELOPMENT IN NORTH TORAJA - Abdullah, Agustina; Rombe, Martha B.; Lestari, Veronica Sri; Anshar, Muhammad; Mawardi, - (Proceeding Buffalo International Conference, 2013)
Enhancement production and productivity of buffalo depends upon three factors, i.e. feeding, breeding and management. The aim of this research was to identify the technology innovation that required by the farmers for buffalo development in North Toraja Regency, South Sulawesi, Indonesia. The research was in North Toraja, South Sulawesi. The farmer samples were determined randomly and its number was determined by Slovin formula. Data were collected by appropriate questioners, focus group discussion (FGD), and deep interview on key informants. The results showed that majority of farmers raise their buffalo traditionally, with buffalo ownership between 2 and 5 heads/households. Almost all buffalo were raised extensively with simple settlement (wooden cages). They grazed on the rice fields or in the dry lands for feeding without farmers guard.Â  In terms of technology innovation, the farmers required such technology improvements as raising system, selection method in breeding, settlements system, feeding and animal health for their animal. Actually, most of the farmers have known some simple technology to fulfill the needs for feeding of their buffalo. However, the application of the technology at farm level was still limited. Therefore, some efforts to optimize application of technology by the farmers are still necessary in order to increase buffalo productivity in North Toraja.